2021
DOI: 10.1186/s13018-021-02581-5
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical study of transsacral-transiliac screw fixation versus lumbopelvic fixation and bilateral triangular fixation for “H”- and “U”-type sacrum fractures with traumatic spondylopelvic dissociation: a finite element analysis study

Abstract: Objective To compare the biomechanical stability of transsacral-transiliac screw fixation and lumbopelvic fixation for “H”- and “U”-type sacrum fractures with traumatic spondylopelvic dissociation. Methods Finite element models of “H”- and “U”-type sacrum fractures with traumatic spondylopelvic dissociation were created in this study. The models mimicked the standing position of a human. Fixation with transsacral-transiliac screw fixation, lumbopel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The modes of fixation for posterior pelvic ring injuries include the screws being inserted only in S1 or in S1 and S2. It has been suggested in biomechanical studies that screw fixation in a double‐layer sacral has higher stability than a single layer, 33,34 and several clinical studies 10,12 obtained the same result, which supported our conclusion that the screw insertion only at the level of S1 had a higher incidence of screw loosening than that inserted at the level of S1 and S2.…”
Section: Discussionsupporting
confidence: 90%
“…The modes of fixation for posterior pelvic ring injuries include the screws being inserted only in S1 or in S1 and S2. It has been suggested in biomechanical studies that screw fixation in a double‐layer sacral has higher stability than a single layer, 33,34 and several clinical studies 10,12 obtained the same result, which supported our conclusion that the screw insertion only at the level of S1 had a higher incidence of screw loosening than that inserted at the level of S1 and S2.…”
Section: Discussionsupporting
confidence: 90%
“…Formal indications of either method have been recently suggested but are not yet widely adopted in clinical practice [3] , [4] , [5] . In traumatic H-/U-type fractures, finite element analyses revealed that LPS is superior to transsacral fixation in terms of translational and rotational stability [6] . Thus, from a biomechanical perspective, single-level transsacral fixation may be considered insufficient in H-/U-type FFP.…”
Section: Discussionmentioning
confidence: 99%
“…Non-displaced U-shaped sacral fractures (AO Spine C0) without neurological deficits can be managed conservatively if the patient suffers from other lesions requiring bed rest. Orthopedic treatment or iliosacral screws can be indicated for slightly displaced Roy-Camille type 1 U-shaped sacral fractures [ 7 , 56 ]. Type 2 and 3 U-shaped sacral fractures (equivalent AO Spine C3) frequently require surgical stabilization.…”
Section: Discussionmentioning
confidence: 99%